2023
DOI: 10.1002/cpdd.1297
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1, Single‐ and Multiple‐Ascending‐Dose, Food‐Effect, and East Asian Subject Studies to Assess the Pharmacokinetics, Safety, and Tolerability of Bempedoic Acid, a Selective Inhibitor of Adenosine Triphosphate Citrate Lyase

Abstract: Bempedoic acid is an adenosine triphosphate citrate lyase inhibitor that lowers low‐density lipoprotein cholesterol by inhibiting cholesterol synthesis and upregulating hepatic low‐density lipoprotein receptor expression. After oral dosing, bempedoic acid was readily absorbed, attaining maximum concentrations with a median time of 3.5 hours, and may be taken without regard to food. Steady‐state oral pharmacokinetics in healthy adults receiving bempedoic acid at the approved 180 mg/day dose were characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As a weak acid, bempedoic acid was also characterized by pH-dependent aqueous solubility, where aqueous solubility is limited under acidic conditions (pH < 6). Although these physicochemical properties align with BCS class two (low solubility, high permeability) drugs [ 3 ], bempedoic acid is much more soluble at pH conditions of the small intestine and is readily absorbed as evidenced by a median time to peak plasma concentration observed at 3.5 h after oral administration [ 4 ]. In addition, human mass balance results indicated that a high fraction of the bempedoic acid oral dose was absorbed after a single [ 14 C] bempedoic acid 240 mg dose administration, where approximately 95% of the dose was absorbed and <5% of the dose was excreted as unchanged drug [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a weak acid, bempedoic acid was also characterized by pH-dependent aqueous solubility, where aqueous solubility is limited under acidic conditions (pH < 6). Although these physicochemical properties align with BCS class two (low solubility, high permeability) drugs [ 3 ], bempedoic acid is much more soluble at pH conditions of the small intestine and is readily absorbed as evidenced by a median time to peak plasma concentration observed at 3.5 h after oral administration [ 4 ]. In addition, human mass balance results indicated that a high fraction of the bempedoic acid oral dose was absorbed after a single [ 14 C] bempedoic acid 240 mg dose administration, where approximately 95% of the dose was absorbed and <5% of the dose was excreted as unchanged drug [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical pharmacokinetics (PK) of bempedoic acid are linear, with dose-proportional increases in systemic exposure observed over a range of 120 to 220 mg/day. Bempedoic acid PK is characterized by an elimination half-life of approximately 21 h, a moderate volume of distribution that is less than total body water, high binding to plasma proteins, and an accumulation ratio of approximately 2.3-fold when dosed daily [ 4 ]. Hepatic metabolism represents the main pathway of elimination, where bempedoic acid is primarily metabolized by uridine 5′ diphospho-glucuronosyltransferase (UGT) 2B7 to form an inactive acyl glucuronide metabolite.…”
Section: Introductionmentioning
confidence: 99%